MATRIX METALLOPROTEINASES 2 AND 9 IN AVOCATION OF MULTITUDINAL COMPLICATIONS IN EXPLICITLY TO CARCINOMA: REVIEW - Robertson, Stellaa; Rajan, Asha K; A, Maheshwaran; B, Senthilnathan; Anuroopa reddy, Sagali Phani Venkata Satya Sai (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Matrix metalloproteinases (MMPs) are a large group of calcium-dependent zinc containing endopeptidases which are mainly concerned with the remodeling of tissue along with degradation of the extracellular matrix. At the present scenario, there is knowledge of about 26 MMPs which are found to be highly regulated by the growth hormones, cytokines, etc., present within the body. At times of normal homeostasis, their levels within the body are low, and their number usually increases at times of pathological conditions. Its generation is known to occur from the pro-inflammatory cells and connective tissues. They may even lead to the process of apoptosis by its interactions with surface receptors. In the clinical trials sectors, various MMPs along with their inhibitors are examined to import the properties of being a high biomarker in the cancer diagnosis, antiangiogenic agents, various other disorders such as chronic allograft nephropathy, diabetic nephropathy, cardiovascular diseases, neuropathic pain, wound healing, angiogenesis processes, immune response, corneal ulceration, embryonic development, and nervous system disorders. As a result, enormous number of studies on this particular enzyme in the marking of cancer and their elevation in the above-mentioned diseases has to be carried out so that it would remain as a useful tool in their diagnosis. The present work is designed to emphasize the concise review of MMPs, in particularly MMP-2 and MMP-9 along with their variant roles, keeping in mind, that it would be advantageous for the researchers to bring out more promising results and to intensify diagnosis of various infirmities, especially in cancer. Keywords: Matrix metalloproteinase-2, Matrix metalloproteinase-9, Biomarker, Matrix metalloproteinases, Carcinoma, Extracellular matrix, Malignancy, Gelatinases, Tumor.